Optimization of biodiesel production from Pungamia oil by Taguchi's technique. Issue 17 (1st September 2016) - Saravanakumar, A.; Avinash, A.; Saravanakumar, R.
ABSTRACT: In biodiesel production process, not all fatty acid chains are turned into alkyl esters (biodiesel). This phenomenon reduces the biodiesel quality and yield significantly. Therefore, optimization of biodiesel production process is very much essential to attain maximum yield. In this work, biodiesel production from raw Pungamia oil was optimized by using Taguchi's method. The L9 orthogonal array was used to optimize the maximum yield of biodiesel production. The parameters like stirrer speed, concentration of NaOH catalyst, and reaction time for producing maximum yield of methyl esters from raw Pungamia oil is reported. In this analysis, signal-to-noise ratio (S/N ratio) and the analysis of variance (ANOVA) are employed to identify and quantify the maximum yield. The analysis revealed that 550 rpm stirrer speed, 15 g of NaOH catalyst, and 80 min reaction time are the optimum parameters for methyl esters of biodiesel production from raw Pungamia oil.